2020
DOI: 10.3390/medicina56040193
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Low-dose Dexmedetomidine Infusion in Sedative Flexible Bronchoscopy: A Retrospective Analysis

Abstract: Background and objectives: Flexible bronchoscopy has been widely used for diagnosis and intervention, while various drugs are used for sedation during bronchoscopy. We examined two regular standardized sedation options (with or without dexmedetomidine) regularly used in our regional hospital. The aim was to assess the efficacy and safety of dexmedetomidine on conscious sedation under bronchoscopy. Materials and Methods: A retrospective chart review was conducted from April 2017 to March 2018. All patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In Figure 6B , the keywords in purple appeared earlier than those in yellow. Yellow circles indicated the newest occurring keywords, including clinical trials of a combination of remifentanil and dexmedetomidine or other methods of sedation ( 20 22 ). For example, it was safer and more comfortable to use deep sedation when removing airway foreign bodies in children, indicating that the application of a combination of remifentanil and dexmedetomidine in painless bronchoscopy might be the priority and hotspot issue in future research on bronchoscopy anesthesia ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 6B , the keywords in purple appeared earlier than those in yellow. Yellow circles indicated the newest occurring keywords, including clinical trials of a combination of remifentanil and dexmedetomidine or other methods of sedation ( 20 22 ). For example, it was safer and more comfortable to use deep sedation when removing airway foreign bodies in children, indicating that the application of a combination of remifentanil and dexmedetomidine in painless bronchoscopy might be the priority and hotspot issue in future research on bronchoscopy anesthesia ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with midazolam, pre-injection of dexmedetomidine before induction significantly decreased the incidence of dreaming in patients undergoing flexible bronchoscopy during general anesthesia; as most dreams were pleasant, patients rarely kept painful memories. The application of dexmedetomidine improved sedative effectiveness with fewer procedural interruptions, shorter time to ambulation, and higher bronchoscopist satisfaction ( 20 , 22 ). Therefore, we need to pay more attention to precision anesthesia and comfort in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of pethidine and midazolam has been shown to be useful in endoscopic pharyngeal observation [23]. However, there is also a report showing the bene t of remimazolam in bronchoscopic sedation [22] and a report showing the bene t of the combination of dextometetodine [24], so the best combination remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in the literature which have used doses of dexmedetomidine lower than the usual 1 μg/kg loading dose. [ 25 ] In one such randomized double-blind study, the investigators found that there was no difference between 0.5 μg/kg of dexmedetomidine and alfentanil 10 μg/kg when used during flexible bronchoscopy. [ 12 ] Thus suggesting that a reduced dose of dexmedetomidine retains its clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%